The effects of L-carnitine on spinal cord ischemia/reperfusion injury in rabbits - Tetik, Ö; Yagdi, T; Islamoglu, F; Calkavur, T; Posacioglu, H; Atay, Y; Yuksel, M (Georg Thieme Verlag Kg, 2002)
Background: Paraplegia after distal aortic aneurysm repair remains a persistent clinical problem. We hypothesized that the tolerance of the spinal cord to an ischemic period could be improved with hypothermic Ringer's Lactate containing L-Carnitine. Materials and Methods: Twenty-eight New Zealand white rabbits were used as spinal cord ischemia models. We separated rabbits into four equal groups and clamped each animal's abdominal aorta distal to the left renal artery. We occluded the aortas above the iliac bifurcation for 30 minutes. In group I, the infrarenal aorta was clamped without infusing any solution. In group II, Ringer's Lactate solution was infused at +25degreesC for 3 minutes at a rate of 5 ml/min into the isolated aortic segments immediately after cross-clamping and the last 3 minutes of ischemia. In group III, Ringer's Lactate solution at +3degreesC was given in the same method as that of group II. In group IV, Ringer's Lactate solution at +3degreesC plus 100 mg/kg of L-carnitine was infused using the same technique. We assessed the neurological status of the hind limbs 24 and 48 hours after operation according to Tarlov's criteria. All animals were sacrificed and spinal cords were harvested for histological analyses. Results: The neurological status in groups III and IV was significantly superior to that of groups I and II. All the animals in group I had complete hind-limb paraplegia. Complete hind-limb paraplegia occurred in 5 rabbits in group II. Two of the 7 animals in group III had spastic paraplegia, and none at all in group IV. Histological analysis of the cross-clamped segments of the rabbits with paraplegia in group I, II and III revealed changes consistent with ischemic injury, while findings were normal for the normal animals in group III and IV. Conclusions: In this model, the infusion of hypothermic Ringer's Lactate contained L-carnitine provided sufficient spinal cord protection against ischemia. Clinically, this may be a useful adjunct for prevention of paraplegia during surgery of the descending aorta.
Keywords: spinal cord protection; L-carnitine; paraplegia; ischemia; reperfusion injury